Entre a potência e o ato: atitudes políticas e percepções de mobilização em Natal e Porto Alegre - Albuquerque Neta, Terezinha Cabral de (2010)
The recent democratic process in Brazil made it as element for its consolidation the idea of participation. It requires a state model that included on its agenda democratic society participation in decision-making process, and a society that has as a principle based participatory civic consciousness. Therefore, this study aims to analyze the level of political participation in two Brazilian state capitals , Natal and Porto Alegre. Data were obtained through quantitative data from the application of 384 questionnaires in both capitals. We chose some variables that will form the basis for our study; Duties of a good citizen, a good citizen rights, Confidence, Index of socialization, exposure to media, degree of interest in politics; Mobilization; Associations. Already qualitative research sought to address the political, cultural and institutional of the two municipalities